Colour appreciation in stress management posters / Siti Azilah Rozalli - Rozalli, Siti Azilah (2019)
This paper studies colour appreciation on past stress management posters. Stress has been defined as an uncomfortable emotional experience that will be followed by physical or psychological pain. Every person will experience stress differently because different individuals will react to the same stressor differently. The issue of stress has been an alarming case especially here in Malaysia. Stress will be one of the major plagues and the percentage of patients that will fall victim to stress will greatly increase. Therefore, a solution is needed to overcome this issue. One of the ways to overcome this is by spreading awareness through a campaign. Posters are one of the items in a campaign as it can give out messages in the form of visuals and texts. To ensure the message is delivered successfully, there are lots of elements and principle of design that need to be taken seriously. One of the most important elements is colour. Colour plays a major role as it is the mood setter in a work. This paper will study on the colour of past stress management posters. A total of five posters were taken from Kementerian Kesihatan Malaysia. The paper will do a descriptive qualitative study on the previous posters. The researcher had studied the colours of the posters using the Feldman’s Method of Art Appreciation, where the researcher will describe the details of the poster, list down the colours that are available, establish meaning behind the colours and lastly give out the researcher’s opinions on how effective the colours are. The researcher had found out that most of the posters by the KKM had been using warm tones and does not tally with the message of stress management. Plus, the researcher had also found that cool colours are more calmly and may deliver the message of stress management more efficiently.